Identification and molecular characterization of novel Rht‐1 alleles in hard red spring wheat. Issue 2 (5th February 2021) - Jobson, Emma M.; Martin, John M.; Sharrock, Robert; Hogg, Andrew C.; Giroux, Michael J.
Abstract: The introduction of the semidwarfing alleles, Rht‐B1b and Rht‐D1b, into wheat ( Triticum aestivum L.) varieties significantly increased wheat yields beginning in the 1960s. Despite their agronomic advantage, Rht‐B1b and Rht‐D1b are also associated with decreased grain protein content and decreased coleoptile length. Furthermore, there is limited allelic diversity available to wheat breeders beyond Rht‐B1b and Rht‐D1b . We identified 16 ethyl methanesulfonate (EMS)‐induced Rht‐1 alleles, including a nonsense mutation in each Rht‐1 gene: Rht‐A‐Q555stop, Rht‐B‐Q420stop, and Rht‐D‐W559stop . We focused our attention for this study on stop alleles since the Rht‐B1b and Rht‐D1b alleles also contain premature stop codons. We evaluated the new nonsense alleles by measuring their impact on coleoptile length, gibberellic acid (GA) sensitivity, and DELLA/GID1 interaction. Rht‐A‐Q555stop reduced coleoptile length 16% compared with Rht‐1a (wild type) and repressed coleoptile GA perception similarly to Rht‐B1b and Rht‐D1b . Rht‐B‐Q420stop and Rht‐D‐W559stop did not affect coleoptile length. However, Rht‐B‐Q420stop reduced the ability of germinating seeds to perceive GA, but not as much as Rht‐A555stop, Rht‐B1b, or Rht‐D1b . We also tested whether the novel mutations affected the interaction between DELLA/GID1 in the presence and absence of GA. We found that Rht‐A‐Q555stop, Rht‐B‐Q420stop, and Rht‐D‐W559stop inhibited DELLA/GID1 interaction in the absence of GA, but the interaction was restored in the presence of GA. The identification of Rht‐A‐Q555stop, Rht‐B‐Q420stop, and Rht‐D‐W559stop increases the allelic diversity of Rht‐1 . This study also indicates that the RHT carboxyl terminus is important for DELLA/GID1 interactions. Core Ideas: New Rht‐1 alleles are generated by EMS mutagenesis. Rht‐1 stop codons near the C terminus affect interactions of RHT with GID1. The RHT C terminus is important for RHT/GID1 interactions.